2021
DOI: 10.1016/j.omtm.2021.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Non-viral ex vivo genome-editing in mouse bona fide hematopoietic stem cells with CRISPR/Cas9

Abstract: We conducted two lines of genome-editing experiments of mouse hematopoietic stem cells (HSCs) with the clustered regularly interspaced short palindromic repeat (CRISPR) and CRISPR-associated protein 9 (Cas9). First, to evaluate the genome-editing efficiency in mouse bona fide HSCs, we knocked out integrin alpha 2b (Itga2b) with Cas9 ribonucleoprotein (Cas9/RNP) and performed serial transplantation in mice. The knockout efficiency was estimated at approximately 15%. Second, giving an example of X-linked severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…For Cas9-mediated gene knockout with RNP transfection, it has been shown that the knockout efficiency ranges from 15 to 90% in various cell types . Similarly, in mouse bona fide hematopoietic stem cells (HSCs), the knockout efficiency of integrin alpha 2b (Itga2b) using Cas9/RNP was estimated to be approximately 15% . In human HEK293 cells, the knockout efficiencies achieved with Cas9/gRNA were 10–25%. , Higher gene knockout levels were also obtained depending on the cell type and delivery method.…”
Section: Discussionmentioning
confidence: 99%
“…For Cas9-mediated gene knockout with RNP transfection, it has been shown that the knockout efficiency ranges from 15 to 90% in various cell types . Similarly, in mouse bona fide hematopoietic stem cells (HSCs), the knockout efficiency of integrin alpha 2b (Itga2b) using Cas9/RNP was estimated to be approximately 15% . In human HEK293 cells, the knockout efficiencies achieved with Cas9/gRNA were 10–25%. , Higher gene knockout levels were also obtained depending on the cell type and delivery method.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with meta-clone 0 (which is multi-potent but more biased towards the Monocyte lineage), meta-clone 4 is also a multi-potent clone but rather biased towards erythrocytes, mast cells and megakaryocytes. Significant genes include Itga2b, which is specifically up-regulated during megakaryopoiesis 56,57 , and Gzmb, which is highly expressed in mast cells and used to degrade hemidesmosomal proteins 58,59 . Interestingly, Akr1c13 and Hbb-bt were also found to be significantly expressed (Fig.…”
Section: Clades Recapitulates the Cellular Dynamics Of Murine Hematop...mentioning
confidence: 99%